(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
In Ayurveda, all skin diseases have been described under the umbrella of Kushtha. Ekakusta is considered as the most commonest skin disease that can affect an individual. Acharya Charak has described the involvement of Vata-Kapha in Eka Kushtha. In the present study Eka kushtha is compared with psoriasis due to resemblance of signs symptoms and causative factors with it. Psoriasis is a papulosquamous disorder of the skin, characterized by sharply defined erythematosquamous lesions this illness exhibits a prompt response if treated carefully, left it may run a very chronic course extending into larger area of the body. Ayurveda focuses more on curative management than palliative management. The drug used in the treatment of Ayurveda does not have complications like modern treatment. Repeated Sodhana prevent the recurrence of the disease. Similarly various preparations have been advocated for the management of Psoriasis. The drugs used in this study are Guduchyadi Kashaya & Rajrukshadi Pachana Kashaya. Both the Kashayas are said to be effective in skin diseases. As per Yogaratnakara, Guduchyadhi Kwath has been mentioned as one of the drug having curative effect on all types of Kustha. Hence for present study the orally Guduchyadi Kwath is taken for EkaKustha treatment. The drugs in Guduchyadi Kwatha are Kusthaghana, Twachya, Swedal, Tridosh shamaka, as well as with Rasayan properties, which is beneficial to break down the pathogenesis of disease. As per Gadanigraha, as mentioned in Kayachikitsakhanda, Rajvrukshadipachana Kashaya is mentioned for the treatment of Ekakushtha. Ingredients in Rajvrukshadi Pachana Kashaya reduce Kapha dosha and most of them act on the skin. Kwatha dravyas are Rasadushtihara, Kaphapittahara, Deepana, Twachya, and also having antibacterial, antimicrobial, antiparasitic and anti-inflammatory properties, Hence, it is helpful for clearing the skin infections.